Efficiency of Pointing Dogs in Locating Northern Bobwhite Coveys - D. Clay Sisson; H. Lee Stribling; Dan W. Speake (National Quail Symposium Proceedings, 2017)
We studied the efficiency of pointing dogs in locating coveys of northern bobwhites (Colinus virginianus) using radiotelemetry from 1992-1997 on 2 private hunting plantations in southwest Georgia. During these 5 hunting seasons, 169 hunts generated data on 838 "encounters" with 254 separate radio-marked coveys. Pointing dogs located 53% of the available coveys, 25% of which were never seen by the hunters due to evasive behavior by the birds. An additional 12% of encountered coveys were seen by the hunters even though they were never located by the dogs. This resulted in the hunters seeing a total of just over half (53%) and shooting into approximately one-third (32%) of the total radio-marked coveys they encountered. An evaluation of "false pointing" was conducted by examining cases when dogs pointed radio-marked coveys that were never seen by the hunters. Most (58%) of these unproductive points were caused by coveys running away from pointing dogs, but were also attributed to wild flushes (28%) and pointed coveys that held tight and refused to flush (14%). The percentage of radio-marked coveys seen by hunters was highly variable from day-to-day (x = 53%, range = 0-100%), but fairly consistent between years (x = 53%, range = 40-63% ). Information obtained using pointing dogs appears to be more practical for measuring population trends than it is as a census technique.